Strong homeostatic TCR signals induce formation of self-tolerant virtual memory CD8 T cells - Drobek, Ales; Moudra, Alena; Mueller, Daniel; Huranova, Martina; Horkova, Veronika; Pribikova, Michaela; Ivanek, Robert; Oberle, Susanne; Zehn, Dietmar; McCoy, Kathy D; Draber, Peter; Stepanek, Ondrej (The EMBO journal, 2018)
Virtual memory T cells are foreign antigen-inexperienced T cells that have acquired memory-like phenotype and constitute 10-20% of all peripheral CD8+ T cells in mice. Their origin, biological roles, and relationship to naïve and foreign antigen-experienced memory T cells are incompletely understood. By analyzing T-cell receptor repertoires and using retrogenic monoclonal T-cell populations, we demonstrate that the virtual memory T-cell formation is a so far unappreciated cell fate decision checkpoint. We describe two molecular mechanisms driving the formation of virtual memory T cells. First, virtual memory T cells originate exclusively from strongly self-reactive T cells. Second, the stoichiometry of the CD8 interaction with Lck regulates the size of the virtual memory T-cell compartment via modulating the self-reactivity of individual T cells. Although virtual memory T cells descend from the highly self-reactive clones and acquire a partial memory program, they are not more potent in inducing experimental autoimmune diabetes than naïve T cells. These data underline the importance of the variable level of self-reactivity in polyclonal T cells for the generation of functional T-cell diversity.
Keywords: Immunologic Memory; receptory antigenů T-buněk; self‐reactivity; Cell Differentiation; Receptors, Antigen, T-Cell; virtual memory T cells; Mice; T‐cell receptor repertoire; CD8-pozitivní T-lymfocyty; gene expression profiling of T‐cell subsets; zvířata; retrogenic T cell; homeostáza; myši; imunologická paměť; buněčná diferenciace; CD8-Positive T-Lymphocytes; Homeostasis; Animals